Effluent Reclamation Through Photocatalysis Using Yb- and Er-Doped Zinc Oxide Nanomaterials - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2025)
Water scarcity and the presence of contaminants of emerging concern (CECs), such as antibiotics, pose significant challenges to sustainable agriculture and public health. In this study, we synthesized and characterized lanthanide-doped zinc oxide (ZnO) photocatalysts (specifically with erbium and ytterbium) to enhance the degradation of sulfamethoxazole (SMX) in wastewater. Utilizing a sol-gel hydrothermal method, we produced various doped ZnO samples and assessed their photocatalytic activity under UV irradiation. The synthesized materials were characterized by powder X-ray diffraction, X-ray photoelectron spectroscopy, UV-vis diffuse reflectance, and SEM-EDX. The ZnO/Yb (5% mol) photocatalyst exhibited the highest degradation rate constant of 3.34 × 10-3 s-1, significantly surpassing undoped ZnO. Mechanistic studies indicated that hydroxyl radicals (•OH) are the primary oxidants driving SMX degradation, as evidenced by quenching tests. Furthermore, we evaluated the performance of the optimized ZnO/Yb photocatalyst in real wastewater samples, achieving an 86% reduction in SMX concentration over 120 min. These findings highlight the potential of lanthanide-doped ZnO as an effective and sustainable solution for mitigating antibiotic pollution in wastewater, contributing to the advancement of photocatalytic technologies for environmental remediation. © 2025 American Chemical Society.